Plan de inversión para el mejoramiento de los procesos productivos en la empresa “publicenter” de la ciudad de Valencia, periodo 2013-2018 - Panchana Arias, Cinthya Stefany (2015)
This Thesis contains the creation of an investment plan to improve the productive processes in the company "PUBLICENTER" located in the Canton Valencia Province of Los Rios in the streets, General Enríquez between(among) García Moreno and December 13, with this one tries to implement machinery of top to offer to the Valencian citizenship quality in the products and services that offer and establish a promotional plan that helps to hand to the company in the mind of the consumers. For the promotional plan will destine anually the quantity of $ 2.200,00 that will allow that the company "PUBLICENTER" should have a major recognition in the local area and bordering cities. For the implementation of new machinery it will be necessary to possess(to rely on) the sum of 59,320.13 $ dollars who will be financed in 100 % by the Corporación Financiara Nacional. The financial study determines that the project is considered to be profitably because has been obtained a VAN positive of $ 48,649.21 and a TIR of 29 % that overcomes the discount tasa of 8.17 %, the above mentioned investment was recovering in 5 years, 4 months and 10 days with a benefit of $ 1.82.